PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 PAGAI UTARA SELATAN - Maryetti, Shummi; Anggraini, Villia; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was conducted for the studentsâ low understanding on mathematics and low cooperative between them in comprehend the material given by the teacher .This research was aimed at revealing whether the use type of cooperative learning Student Team Achievement Division ( STAD ) on the students comprehension ofÂ mathematical concept than the conventional learning in class VII of SMPN 1 Pagai Utara Selatan. This research is an experimental study . This was an experimental research which used random toward the subject design. Hypothesis test results obtained tcalculated = 2.07 and ttable= 1.669,Â indicating that the hypothesis was accepted. So, it was concluded that the application ofÂ Student Team Achievement Division ( STAD ) could improve the students comprehension ofÂ mathematical concept better than the conventional learning SMPN 1 Pagai Utara Selatan with 95% confidence level . ( Î± = 0.05 )